Faint traces of a human figure visible on the stone fragment - Temples of India Project Team (Jio Institute, 2024)
Seen here what appears to be a sculptural fragment among the row of hero stones. This speculation is drawn from faint traces of a human figure visible on the stone fragment. Given that the collection includes not only hero stones but also other pieces, it is plausible that a broken sculpture is venerated as a hero stone. Unlike other Hero stones, this fragment has a low pedestal.